Factors associated with the efficiency of university teaching activity (SCIÉNDO INGENIUM, 2024)
The objective of the research was to determine the factors associated with the efficiency of the university teacher's activity, with a descriptive, observational and transversal scope. The population was considered as university students and teachers of a Private University Education Institution of Trujillo with a total of 112 students and 42 teachers, to whom two questionnaires were applied, one for each variable, validated by three experts and the reliability test was carried out, by means of Cronbach's alpha. It was concluded that the factors associated with the efficiency of university teaching activity from the perspective of students and teachers, respectively, are: pedagogical (53.6%, 66.7%); human (49.1%, 69%); and ideological (48.2%, 61.9%). The level of achievement in the efficiency of university teachers from the students' perspective is medium 46.4% and high 52.4% from the teachers' perspective; the efficiency in the academic dimension and university social responsibility is medium represented by 49.1% and 53.6% respectively, while the research dimension is high with 45.5% for students and from the teachers' perception the opposite was identified, where the academic, research and university social responsibility efficiency is high with 69% and 66.7% respectively.
Keywords: Pedagogical factors; human; ideological; efficiency